2022
DOI: 10.1371/journal.pone.0264158
|View full text |Cite
|
Sign up to set email alerts
|

Motivations, barriers and exercise preferences among female undergraduates: A need assessment analysis

Abstract: Introduction The decreasing level of physical activity among female undergraduates is worrying as it is associated with the increased risk of non-communicable diseases. Thus, this study aimed to identify the motivations, barriers and preferences towards exercise among female undergraduates in Malaysia. Methods A non-probability purposive sampling was used for the recruitment process. The inclusion criteria of the participants were registered female undergraduates and aged between 18–30 years old. A semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 56 publications
2
12
0
3
Order By: Relevance
“…Moreover, this study showed that lack of time, convenience, and knowledge on how to make healthy food choices were barriers to eating healthier, limiting weight loss success [ 49 ]. Previous studies also showed that busy schedules, lack of time for meal preparation and exercise, emotional eating, stress, depression, low self-esteem, family responsibilities, cultural norms, and lack of social support were identified as significant barriers [ 6 , 50 , 51 ], consistent with our findings. Another previous study showed that, for children with obesity, an unemployed father (OR=11.90; 95% CI: 7.47-18.93), a father with overweight or obesity (OR=2.04; 95% CI: 1.40-2.96), an incorrect parental perception of the child’s weight status (OR=2.54; 95% CI: 1.75-3.68), physical activity for less than 30 min (OR=2.18; 95% CI: 1.44-3.28), frequent snacking (OR=1.74; 95% CI: 1.05-2.93), and screen time use for more than 2 hours per day outside of school (OR=1.62; 95% CI: 1.12-2.34) were associated with weight gain and unsuccessful weight loss efforts [ 52 ].…”
Section: Reviewsupporting
confidence: 92%
“…Moreover, this study showed that lack of time, convenience, and knowledge on how to make healthy food choices were barriers to eating healthier, limiting weight loss success [ 49 ]. Previous studies also showed that busy schedules, lack of time for meal preparation and exercise, emotional eating, stress, depression, low self-esteem, family responsibilities, cultural norms, and lack of social support were identified as significant barriers [ 6 , 50 , 51 ], consistent with our findings. Another previous study showed that, for children with obesity, an unemployed father (OR=11.90; 95% CI: 7.47-18.93), a father with overweight or obesity (OR=2.04; 95% CI: 1.40-2.96), an incorrect parental perception of the child’s weight status (OR=2.54; 95% CI: 1.75-3.68), physical activity for less than 30 min (OR=2.18; 95% CI: 1.44-3.28), frequent snacking (OR=1.74; 95% CI: 1.05-2.93), and screen time use for more than 2 hours per day outside of school (OR=1.62; 95% CI: 1.12-2.34) were associated with weight gain and unsuccessful weight loss efforts [ 52 ].…”
Section: Reviewsupporting
confidence: 92%
“… 52 , 53 Lipid parameters (TG/HDL-C, LDL-C/HDL-C, and CHOL/HDL-C ratios) have been linked to the risk of CVD. 35 , 36 Urbina et al. (2013) found that a higher TG/HDL-C value was correlated with an increase in weight, heart rate, and risk of diabetic complications in adolescents and young adults, especially in obese youth.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of motivation was reported by participants as one of the barriers to engaging in high-intensity exercises among female undergraduates. 35 The causes of physical inactivity are multifactorial, including a lack of access to the necessary facilities, time, exercise partner, and confidence. 36 Thus, the present study sought to investigate how a 12-week, 10,000 steps per day, walking exercise influenced the body composition, serum lipids, adipose tissue function, and obesity-associated cardiometabolic risk in young adult women from two weight groups, overweight and normal.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well established that exercise promotes health benefits, the uptake and adherence of the exercise programs in all populations including obese individuals are generally low due to a number of reasons including lack of time and motivation [ 76 , 77 , 78 ]. Recently, technology-based interventions have become a part of healthcare and medical intervention, providing accessible and motivational benefits for health promotion [ 32 , 79 ].…”
Section: Technology-based Interventions For Health and Cognitive Bene...mentioning
confidence: 99%